2020
DOI: 10.3390/jcm9051276
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns Distinguish Mortality Risk in Patients with Postsurgical Shock

Abstract: Nowadays, mortality rates in intensive care units are the highest of all hospital units. However, there is not a reliable prognostic system to predict the likelihood of death in patients with postsurgical shock. Thus, the aim of the present work is to obtain a gene expression signature to distinguish the low and high risk of death in postsurgical shock patients. In this sense, mRNA levels were evaluated by microarray on a discovery cohort to select the most differentially expressed genes between surviving and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Some of the key genes in our study ( ANXA3 and CD177 ) have been previously reported to be involved in sepsis, while GRAMD1C and TIGD3 have not [ 26 29 ]. GRAMD1C is a featureless protein belonging to the gram domain protein family [ 30 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some of the key genes in our study ( ANXA3 and CD177 ) have been previously reported to be involved in sepsis, while GRAMD1C and TIGD3 have not [ 26 29 ]. GRAMD1C is a featureless protein belonging to the gram domain protein family [ 30 ].…”
Section: Discussionmentioning
confidence: 85%
“…In addition, CD177 combined with other genes ( IL1R2 , OLFM4 , and RETN ) has been reported as a potential indicator of prognosis in patients with sepsis. Compared with the Acute Physiology and Chronic Health Evaluation and Sequential Organ Failure Assessment scores, CD117 has more advantages in estimating the prognosis of patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GEO (http://www.ncbi.nlm.nih.gov/geo) database is a public functional genomics data repository of high-throughput gene expression data, chips, and microarrays [12] . Two datasets, GSE131761 [13] and GSE94717 [14] , met our retrieval requirement for this study. The differentially expressed mRNAs and miRNAs between healthy controls and samples collected from patients who experienced sepsis were identified using the web tool named GEO2R (http://www.ncbi.nlm.nih.gov/geo/geo2r).…”
Section: Methodsmentioning
confidence: 99%
“…The author observed a constant subset of neutrophils that did not express CD177, while simultaneously, neutrophils from septic patients had increased CD177 both mRNA and protein expression (70). Moreover, significantly elevated transcription of CD177 was found in non-survivors compared with survivors after post-surgical shock (71). Increased CD177 expression was also reported in rat lung tissue in cecal ligation and puncture (CLP)-induced sepsis but not in blood or liver (72).…”
Section: Surface Markersmentioning
confidence: 96%